Certificate authentication system using QR code - Chan, Ming Ting (2014)
Due to the competitive situation in getting a good job, people tend to fraud their academic certificate. However, the origin authentication technique takes a long time to certify a certificate. Thus, in this paper, a certificate authentication system using QR code is developing for makeup easier way for authenticate certificate. This project is used SDLC to manage the development of system while QR technology is used to increase the usability and functionality of system. At the end of project, this system has effective reduction on the time taken for authenticate a certificate. By that, company does have a medium to check the originality of certificate easily.